2012
DOI: 10.1182/blood.v120.21.1472.1472
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Day 28 Absolute Lymphocyte Count On Outcome of Hematopoietic Cell Transplant (HCT) in CR1 for Adult Patients with Acute Lymphoblastic Leukemia

Abstract: 1472 Introduction: Despite significant advances in survival rates for pediatric Acute Lymphoblastic Leukemia (ALL) patients (pts), long-term survival rates for adults with ALL have remained below 40%. An absolute lymphocyte count (ALC) < 350/μL at Day 28 of induction therapy is predictive of poor outcome [event-free survival (EFS) and overall survival (OS)] in adults with newly diagnosed ALL. It is unknown, however, whether ALC at Day 28 is also predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another study demonstrated that absolute lymphocyte count (ALC) >0.3 × 10 9 /L at day 30 postalloHCT for acute leukemia was strongly associated with improved OS . Other studies have examined ALC recovery at 28 d postalloHCT for acute lymphoblastic leukemia (ALL), demonstrating an ALC <0.25 × 10 9 /L to be associated with decreased leukemia‐free survival (LFS) and OS .…”
mentioning
confidence: 99%
“…Another study demonstrated that absolute lymphocyte count (ALC) >0.3 × 10 9 /L at day 30 postalloHCT for acute leukemia was strongly associated with improved OS . Other studies have examined ALC recovery at 28 d postalloHCT for acute lymphoblastic leukemia (ALL), demonstrating an ALC <0.25 × 10 9 /L to be associated with decreased leukemia‐free survival (LFS) and OS .…”
mentioning
confidence: 99%